2015
DOI: 10.1161/circep.114.002553
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 2014 European Society of Cardiology Guidelines Risk Prediction Model for the Primary Prevention of Sudden Cardiac Death in Hypertrophic Cardiomyopathy

Abstract: Background-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
2
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 30 publications
5
77
2
7
Order By: Relevance
“…The C-statistic for the HCM risk-SCD model has been reported to be 0.70 14 with external validation yielding a C-statistic of 0.69. 29 Interestingly T-wave amplitude did not augment the HCM risk-SCD model and at baseline this model was not significant in our cohort. We were missing data on eight individuals so this may contributed and this may be reflective regional phenotypic variations in HCM cohorts.…”
Section: Discussioncontrasting
confidence: 53%
“…The C-statistic for the HCM risk-SCD model has been reported to be 0.70 14 with external validation yielding a C-statistic of 0.69. 29 Interestingly T-wave amplitude did not augment the HCM risk-SCD model and at baseline this model was not significant in our cohort. We were missing data on eight individuals so this may contributed and this may be reflective regional phenotypic variations in HCM cohorts.…”
Section: Discussioncontrasting
confidence: 53%
“…Independent, external comparison of these two approaches has shown that the HCM-risk SCD model improves the risk stratification of patients with HCM (C statistic 0.69) compared to 2011 ACCF/AHA guidelines (Cstatistics 0.6). 16 However, whilst advances have been made in risk stratification for adult patients, little progress has been made in risk stratification for childhood HCM. Indeed, although a large number of potential risk factors for SCD have been reported in the literature over the past 30 years, the lack of consistent definitions and well-designed, large population studies means that the evidence for individual risk factors is not robust.…”
Section: Childhood Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…2 Furthermore, 2 groups have now examined how the guidance would have performed in their patients and arrived at essentially polar opposite conclusions on utility. 3,4 Article see p 829…”
mentioning
confidence: 99%
“…1,6 Such progress has had a significant impact on improving patient outcomes, but there is the critical issue that we remain only modestly capable of identifying accurately the small subset that will benefit from an ICD. 1,3,4,8 Why risk prediction remains so difficult has been extensively considered. 1,5 Despite large patient cohorts, it is the phenotypic diversity of HCM, the low SCD event rates, the long recruitment periods, evolving assessment methods and corresponding incomplete data that have all confounded clear answers.…”
mentioning
confidence: 99%
See 1 more Smart Citation